Health Promotion Strategy on Disease Management Efforts Dengue Hemorrhagic Fever (DHF) in Health Office of Wajo Distric - Herman Herman; Fifi Andriani (Jurnal Farmasi Sandi Karsa, 2021)
Dengue Hemorrhagic Fever (DHF) is a deadly disease, transmitted by the Aedes aegypti and Aedes albopictus mosquitoes which carry the dengue virus. Data on dengue cases at the Wajo District Health Office from the last 5 years, in 2015 there were 199 cases, in 2016 there were 281 cases, in 2017 there were 29 cases, in 2018 there were 60 cases and in 2019 there were 297 cases. Based on the results of observations at the Wajo District Health Office, there are strategies carried out by the Health Office in the form of advocacy, social support, partnerships and community empowerment. The purpose of this study was to determine the health promotion strategy for the prevention of dengue hemorrhagic fever (DHF) at the Wajo District Health Office. This study uses a qualitative method with a Phenomenology approach. Collecting data in research by conducting in-depth interviews. Determination of research subjects using purposive sampling with the criteria that Wajo District Health Office employees, Tempe Health Center employees and willing to be interviewed. The results showed that the advocacy carried out by the Wajo District Health Office in dealing with dengue disease was advocacy to the leadership of BAPEDA, DPRD and Puskesmas in budget proposals. Social support, namely the existence of cooperation between RT/RW officials, NGOs and community leaders in efforts to control DHF. The partnership is the coordination between the Health Office, Local Government, Education Office, and Regional Coordinator in eradicating mosquito nests (PSN). Community empowerment, namely larval monitoring or jumantik training for cadres and the community as well as doing community service to clean the environment.